Proyecto de creación de un Centro Gerontológico Ocupacional y Recreativo en el Cantón Playas. - Alay Loor, Olga María (2010)
This research was conducted under the methodological guidelines and regulations established by the University for this purpose. Thus was once given the topic, an analysis of the problem by considering the causes and consequences that failure to have the county Beaches and Recreation Gerontological center that provides specialized care for older persons, which fully justified realization. Stated objectives (general and specific), identified the need to provide us with the necessary resources that the investigation requires, and the hypothesis guided the research process. In literature review, this was carefully selected to provide sufficient information to date and relevant object of study. In terms of research-based field surveys and interviews, yielded some interesting information and data source in which, among other things, it makes a diagnosis of the situation in which older adults live for lack of occupational Gerontology Center and recreational beaches in the county, results were subjected to an objective discussion with a view to establish its theoretical implications, and in turn get to test the hypothesis. With the results of the investigation, which determines the need for a geriatric center in this county, was made an alternative proposal justifying the need for the creation of such a care center for adults / as adults. Finally, the conclusions were drawn where it is determined to achieve the goals that we considered, and recommendations that warrant the case. The size of the project is 23.27% of the demand for the first year, ie 300 persons will be served. Fixed investment in fixed assets and deferred amounts to the amount of $ 288,567.68. Operating capital for the first three months is $ 55,066.50. Fixed costs and variable $ 239,057.96 $ 2,466.00. For the first year: the income is $ 10,500.00, the income statement is $ (233,723.96), the cash flow generated is (205,003.30) dollars, the monetary equilibrium is 312,435.72 and updated cost benefit ratio is 0.07. The TIR is 0%